(3 2/3+17 1/5)−(11 3/5+2 1/3)

1 answer

To solve the expression \((3 \frac{2}{3} + 17 \frac{1}{5}) - (11 \frac{3}{5} + 2 \frac{1}{3})\), we will first convert the mixed numbers to improper fractions, perform the necessary addition and subtraction, and then convert back to a mixed number if necessary.

Step 1: Convert mixed numbers to improper fractions.

  1. Convert \(3 \frac{2}{3}\): \[ 3 \frac{2}{3} = \frac{3 \times 3 + 2}{3} = \frac{9 + 2}{3} = \frac{11}{3} \]

  2. Convert \(17 \frac{1}{5}\): \[ 17 \frac{1}{5} = \frac{17 \times 5 + 1}{5} = \frac{85 + 1}{5} = \frac{86}{5} \]

  3. Convert \(11 \frac{3}{5}\): \[ 11 \frac{3}{5} = \frac{11 \times 5 + 3}{5} = \frac{55 + 3}{5} = \frac{58}{5} \]

  4. Convert \(2 \frac{1}{3}\): \[ 2 \frac{1}{3} = \frac{2 \times 3 + 1}{3} = \frac{6 + 1}{3} = \frac{7}{3} \]

Step 2: Combine the fractions for the additions.

  1. Calculate \(3 \frac{2}{3} + 17 \frac{1}{5}\): \[ \frac{11}{3} + \frac{86}{5} \] Find a common denominator, which is 15: \[ \frac{11}{3} = \frac{11 \times 5}{3 \times 5} = \frac{55}{15} \] \[ \frac{86}{5} = \frac{86 \times 3}{5 \times 3} = \frac{258}{15} \] Now add the two: \[ \frac{55}{15} + \frac{258}{15} = \frac{55 + 258}{15} = \frac{313}{15} \]

  2. Calculate \(11 \frac{3}{5} + 2 \frac{1}{3}\): \[ \frac{58}{5} + \frac{7}{3} \] Again, use a common denominator of 15: \[ \frac{58}{5} = \frac{58 \times 3}{5 \times 3} = \frac{174}{15} \] \[ \frac{7}{3} = \frac{7 \times 5}{3 \times 5} = \frac{35}{15} \] Now add these: \[ \frac{174}{15} + \frac{35}{15} = \frac{174 + 35}{15} = \frac{209}{15} \]

Step 3: Subtract the two results.

Now we subtract the two sums: \[ \frac{313}{15} - \frac{209}{15} = \frac{313 - 209}{15} = \frac{104}{15} \]

Step 4: Convert back to a mixed number.

To convert \(\frac{104}{15}\) to a mixed number:

  • Divide \(104\) by \(15\):
    • \(104 \div 15 = 6\) remainder \(14\). So, \(\frac{104}{15} = 6 \frac{14}{15}\).

Final Answer

\[ (3 \frac{2}{3} + 17 \frac{1}{5}) - (11 \frac{3}{5} + 2 \frac{1}{3}) = 6 \frac{14}{15} \]